The Influence of Leadership Style and Work Motivation On Job Engagement Mediated By Job Satisfaction - Chandra, Yudhi; Wibowo Widhianto, Chandra (Jurnal Indonesia Sosial Sains, 2023)
The aim of this research aims to determine the influence of leadership style and work motivation on work engagement which is mediated by job satisfaction. Research methods and data were obtained from distributing questionnaires via Google Form. Samples were taken using purposive sampling technique. This research uses quantitative analysis techniques and is processed using PLS. This research uses the variables Leadership Style and Work Motivation as the dependent variable, Work Engagement as the independent variable, and Job Satisfaction as the Mediating variable. The results of this research show that Leadership Style has a positive and significant effect on Work Engagement, Work Motivation has a positive and significant effect on Work Engagement. Leadership Style has a positive and significant effect on Job Satisfaction, Work Motivation has a positive and significant effect on Job Satisfaction, Job Satisfaction has a positive and significant effect on work engagement, Job Satisfaction has a positive and significant mediating effect on Leadership Style on work engagement, Job Satisfaction has a positive and significant mediating effect Work Motivation on Work Engagement. It is hoped that the implications and recommendations from this research can be input for the company PT. XYZ in Jakarta to determine the influence of leadership style and work motivation on work engagement which is mediated by job satisfaction. So that later it will strengthen and expand the implications of PT. XYZ in Jakarta